Grammatical Errors in Movie Titles: Syntax and Semantic Analysis - Gusti Putri Qadriah; Heri Heryono (Budapest International Research and Critics University, 2022)
The purposes of this research are to identify grammaticaly errors in movie titles and to find out linguistics elements that are put together to form constituents (such as phrases or clauses) and analyze the process of drawing meaning from the text. This study was carried out by qualitative descriptive method and content analysis approach. Since the content is in the form of a written document containing transcripts of several movies titles, it is categorised as documentation. The titles of the movies researched are several movies from various genres and various years of release. The theories used in this research are James (1998) about grammatical errors, Purnomoadjie and Mulyadi (2019) about syntactical analysis and Gada (2020) linguistics competence and error analysis. From the results of the analysis, it was found that types of grammatical errors are divided into five types; general grammatical errors, substance errors, lexical errors, syntactic errors and semantic errors. From 30 data analyzed previously, there are only three categories of grammatical error found. The first is general grammatical errors by the 57% of data, while semantic errors 31%, and substance error has 12%. There are no data for lexical and syntactic error in movie titles. The types of grammatical errors found in the movies is commonly general grammatical errors; thus, it can be concluded that the titles of the movies have commonly grammatical errors.